Enhancing Complex Problem Solving (CPS) and Environmental Awareness Through the Development of STEM-Integrated E-Worksheets - Andri, Mutiara Caesara; Jalmo, Tri; Abdurrahman, Abdurrahman; Lengkana, Dewi (International Journal of Education, Culture, and Society, 2025)
One of the key challenges in 21st-century education is students' limited ability to address complex, real-world problems, particularly those related to global environmental issues. Complex Problem Solving (CPS) has been identified as an essential skill for navigating such challenges; however, CPS proficiency among Indonesian students remains relatively low, especially in the context of environmental awareness. This study aims to develop a differentiated STEM-integrated electronic worksheet (e-worksheet) designed to enhance CPS skills and foster environmental awareness among junior high school students. Employing a Research and Development (R&D) approach based on Thiagarajan’s 4D model, Define, Design, Develop, and Disseminate, the study began with a needs analysis involving 15 teachers and 200 students from nine schools in Lampung Province. The STEM-based e-worksheet was developed with a focus on CPS indicators and environmental themes. Implementation was conducted with 26 seventh-grade students from SMP Negeri 12 Bandar Lampung. Data were collected through pre-test and post-test instruments and analyzed using normalized gain (n-gain) and effect size metrics. Results showed that the use of the e-worksheet significantly improved students’ CPS abilities, with an n-gain of 0.56 (moderate) and an effect size of 4.12 (high), indicating substantial progress across all CPS dimensions. These findings highlight the potential of differentiated, STEM-oriented digital learning tools to enhance critical 21st-century skills and support environmental education at the junior secondary level.